Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsomega.1c02981
|View full text |Cite
|
Sign up to set email alerts
|

ZnO and TiO2 Nanocolloids: State of Mechanisms that Regulating the Motility of the Gastrointestinal Tract and the Hepatobiliary System

Abstract: Using the transmission electron microscopy (TEM)/high-resolution TEM (HRTEM) and selected area electron diffraction (SAED) methods, it was shown that the nanocolloids of ZnO contain hydrolyzed ZnO nanoparticles (NPs). Typically, the nanocrystalline ZnO/Zn­(OH)2 core is covered by an amorphous shell of zinc hydroxides, preventing the encapsulated crystal core from dissolving. Similar studies were carried out with TiO2 nanocolloids. It was found that burdening of rats for 30 days with a ZnO aqueous nanocolloid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…3, 4.3, 5.3). A comparison of the above results with the previously obtained data 2 about the state of the mechanisms of regulation of the spontaneous contractile activity of SMs in different parts of GIT under short-term (30 days) intragastrically burdening of rats with TiO 2 AN showed (Figs. 3, 6) that they underwent the greatest changes under the long-term exposure, while under otherwise the same conditions, the results of burdening with ZnO AN were the opposite.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…3, 4.3, 5.3). A comparison of the above results with the previously obtained data 2 about the state of the mechanisms of regulation of the spontaneous contractile activity of SMs in different parts of GIT under short-term (30 days) intragastrically burdening of rats with TiO 2 AN showed (Figs. 3, 6) that they underwent the greatest changes under the long-term exposure, while under otherwise the same conditions, the results of burdening with ZnO AN were the opposite.…”
Section: Resultssupporting
confidence: 66%
“…According to the literature 31 , age-related changes in the body cause partial loss of ICC (13% per decade for the human body aged 25-74 years) and the development of pathologies. A comparison of the above values of the spontaneous contractions parameters of the antrum piloricum and caecum SMs of rats (control group, age eight months) with the values of the corresponding parameters in rats of the younger age group (control group, age three months), reported in our previous study 2 , showed that in the older age group of rats, the frequency of spontaneous contractions of both the antrum pyloricum and the caecum SMs was almost twice lower than in the younger age group, n = 12. The duration of contraction-relaxation cycles increased; the amplitude ranges were nearly identical, whereas the amplitudes of contractions of the antrum SMs were three times higher than the corresponding value for the younger age group.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation